Linking Corporate Social Responsibility to Corporate Performance: Evidence from the Media Industry - Miroslav Ivić (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
This study explores the interdependence of corporate social responsibility (CSR) and corporate performance using a sample of companies from the media industry in the Republic of Croatia. Our primary aim was to empirically test hypothesized positive relationship between CSR and corporate performance. We identified core CSR dimensions of companies operating in the media industry (relationship with owners, employees, stakeholders, environment, and society) and applied the new methodological approach in CSR classification through criteria of (under)development. Our results suggest that corporate performance measured by a composite indicator based on the Balanced Scorecard in companies with developed CSR is statistically significantly higher than for the companies with underdeveloped CSR.
Keywords: 650; corporate social responsibility (CSR); corporate performance; Balanced Scorecard; media industry